Pengaruh Transcutaneous Electrical Auricular Acupressure Stimulation (Teaas) Terhadap Xerostomia dan Rasa Haus pada Pasien CKD yang Menjalani Hemodialisis - Fhadilah Rahmadini; Ta'adi Ta'adi; Budi Widiyanto; Suharsono Suharsono; Sri Endang Windiarti (Universitas Malahayati Lampung, 2026)
ABSTRACT Chronic Kidney Disease (CKD) patients undergoing hemodialysis often experience xerostomia and excessive thirst, which impact their comfort and quality of life. Available interventions are limited, necessitating alternative non-pharmacological approaches such as Transcutaneous Electrical Auricular Acupressure Stimulation (TEAAS). Analyzed the effect of TEAAS on reducing xerostomia and thirst in CKD patients undergoing hemodialysis and compared its effectiveness with a control intervention (gargling with boiled water). This study used a quasi-experimental design with a pre-test and post-test with a control group. A sample of 34 respondents was selected using purposive sampling and divided into the intervention (TEAAS) and control (gargling with boiled water) groups. The interventions were administered six times over three weeks. Measurements were made using the SXI-ID and TDS. Data were analyzed using the Wilcoxon, Mann–Whitney, and GEE tests. Results: TEAAS significantly reduced xerostomia (p 0,001) and thirst (p 0,001), with better results compared to the control group. There were significant differences between groups at post-test for xerostomia (p = 0,007) and thirst (p = 0,008). Fluid hydration status significantly influenced both variables (p 0,001). TEAAS is more effective than gargling with boiled water in reducing xerostomia and thirst in CKD patients undergoing hemodialysis, and hydration status is a significant influencing factor. Keywords: Chronic Kidney Disease, Hemodialysis, Transcutaneous Electrical Auricular Acupressure Stimulation, Xerostomia, Thirst. ABSTRAK Pasien Chronic Kidney Disease (CKD) yang menjalani hemodialisis sering mengalami xerostomia dan rasa haus berlebih yang berdampak pada kenyamanan serta kualitas hidup. Intervensi yang tersedia masih memiliki keterbatasan sehingga diperlukan pendekatan nonfarmakologis alternatif seperti Transcutaneous Electrical Auricular Acupressure Stimulation (TEAAS). Menganalisis pengaruh TEAAS terhadap penurunan xerostomia dan rasa haus pada pasien CKD yang menjalani hemodialisis serta membandingkan efektivitasnya dengan intervensi kontrol (berkumur air matang).Penelitian ini menggunakan desain quasi experimental dengan pre-test dan post-test with control group. Sampel berjumlah 34 responden yang dipilih secara purposive sampling dan dibagi menjadi kelompok intervensi (TEAAS) dan kontrol (berkumur air matang). Intervensi diberikan sebanyak enam kali selama tiga minggu. Pengukuran menggunakan SXI-ID dan TDS. Analisis data menggunakan uji Wilcoxon, Mann–Whitney, dan GEE. Hasil: TEAAS secara signifikan menurunkan xerostomia (p 0,001) dan rasa haus (p 0,001), dengan hasil yang lebih baik dibandingkan kelompok kontrol. Terdapat perbedaan signifikan antar kelompok pada post-test untuk xerostomia (p = 0,007) dan rasa haus (p = 0,008). Status hidrasi cairan berpengaruh signifikan terhadap kedua variabel (p 0,001). TEAAS lebih efektif dibandingkan berkumur air matang dalam menurunkan xerostomia dan rasa haus, serta status hidrasi menjadi faktor yang memengaruhi kedua kondisi tersebut. Kata Kunci: Chronic Kidney Disease, Hemodialisis, Transcutaneous Electrical Auricular Acupressure Stimulation, Xerostomia, Rasa Haus.